Modulation of drug crystallization and molecular interactions by additives in solid dispersions for improving drug bioavailability - Tran, Phuong H.L.; Duan, Wei; Lee, Beom Jin; Tran, Thao T.D. (Current Pharmaceutical Design, 2019)
Background: An increase in poorly water-soluble drugs makes the design of drug delivery systems challenging. Methods: Currently, a number of prospective solid dispersions have been investigated with potential applications for delivering a variety of poorly water-soluble drugs. A number of traditional solid dispersions and modified-solid dispersions offer attractive advantages in the fabrication, design and development of those drugs for effective therapeutics. Results: Although traditional solid dispersions can produce a higher release rate, resulting in higher bioavailability compared to conventional dosage forms, this method is not always a promising approach. Modified-solid dispersion has demonstrated both the ability of its polymers to transform drug crystals into amorphous forms and molecular interactivity, thereby improving drug dissolution rate and bioavailability, especially with tough drugs. However, the classification of modified-solid dispersion, which guides the selection of the right strategy in solid dispersion preparation, remains ill-defined. Conclusion: This review focused on effective strategies in using additives in solid dispersion for improving drug bioavailability.
Keywords: Biological Availability; Crystallization; Pharmaceutical Preparations; Solubility; Additive; Hydrophobic polymer; Modified-solid dispersion; PH-modifier; Poorly water-soluble drug; Surfactant; Swellable polymer